2020
DOI: 10.1080/14787210.2020.1822735
|View full text |Cite
|
Sign up to set email alerts
|

Alanine transaminase and hemoglobin appear to predict the occurrence of antituberculosis medication hepatotoxicity; findings and implications in Botswana

Abstract: Objective: Tuberculosis (TB) remains a global health problem, with medications having adverse effects including drug-induced hepatotoxicity. We determined the prevalence of anti-tuberculosis druginduced hepatotoxicity and associated risk factors. Methods: Retrospective cross-sectional study in Botswana including TB patients admitted from 1 June 2017 to 30 June 2018. Anti-TB drug-induced hepatotoxicity was categorized according to WHO criteria whereas causality assessment was made according to the updated Rouss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…We also compared baseline ALT and hemoglobin levels in both the ATDH and non-ATDH groups and showed no statistical difference between the two groups. The previous study has shown a signi cant correlation between baseline ALT levels and ATDH [30]. In their study, normal baseline levels of hemoglobin were also signi cantly correlated with ATDH.…”
Section: Strati Cation Analysismentioning
confidence: 64%
“…We also compared baseline ALT and hemoglobin levels in both the ATDH and non-ATDH groups and showed no statistical difference between the two groups. The previous study has shown a signi cant correlation between baseline ALT levels and ATDH [30]. In their study, normal baseline levels of hemoglobin were also signi cantly correlated with ATDH.…”
Section: Strati Cation Analysismentioning
confidence: 64%
“…China is the third largest source of new TB cases globally, and it accounts for 8.4% of the global total ( WHO, 2020 ). However, most of the first-line drugs used to treat TB have potential hepatotoxic effects ( Kesenogile et al, 2021 ). Drug-induced Liver Injury (DILI) is an injury to the liver or biliary system associated with the ingestion of hepatotoxic drugs, and it is one of the most common causes of acute liver failure ( Devarbhavi et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%